Novice English teachers’ knowledge about assessment of learning, assessment for learning, and assessment as learning - Eka Anastasia Wijaya (ELT Forum: Journal of English Language Teaching, 2023)
This study aimed to investigate the novice English teachers’ knowledge about assessment of learning, assessment for learning, and assessment as learning in the context of Bali. Framed within a qualitative design, the study employed the qualitative method with a questionnaire and an interview guide as the instruments to collect the data. The obtained data were analysed using Interactive Model Analysis consisted of data collection, data display, data reduction, and verification or conclusion drawing. In the preliminary informal interview done towards several novice English teachers, it indicated that not all novice English teachers have heard about assessment of learning, assessment for learning, and assessment as learning. Therefore, this phenomenon led the researcher to conduct this study. Further, the results of this study showed that the novice English teachers’ knowledge about assessment of learning, assessment for learning, and assessment as learning are limited to the basic concepts only. Even, several novice English teachers never heard about those assessment types. It implies that the school principals and other stakeholders need to emphasize the concept of assessment of learning, assessment for learning, and assessment as learning for novice English teachers through teacher training, workshop, or seminar.